PENCAPAIAN STANDAR PELAYANAN MINIMAL BIDANG PELAYANAN DASAR PADA PEMERINTAH DAERAH KOTA PEKANBARU PROVINSI RIAU - Maulidiah, Sri; Husna, Asmaul (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
In the system of Government of the Unitary State of the Republic of Indonesia, Regional Government is a sub-system of the national government, local governments are obliged to provide public services in the implementation of governmental affairs in accordance with minimum service standards (SPM) governed by the Central Government. In its development, up to 2012 has been determined as many as 15 affairs with SPM at the district / city level consists of 65 types of services and 276 service indicators (including sub indicators). The time limit of SPM achievement ranges from 2013-2025. This study uses a qualitative method. The result of the research shows that until 2014, Pekanbaru Municipal Government has implemented 15 fields, with 210 (76,09%) reporting indicators and service indicators reaching 116 national indicators or 42.03%. There are 3 SPM affairs with 100% reporting indicator that is, Environment, Family Planning and Family Welfare and Employment. While 11 of the 15 other affairs reported between 33.33 - 95.45%, communication and information affairs that have the smallest percentage, the percentage of service indicators reach the national target, the Environment has the largest percentage of 100 percent of 4 indicators of service, with the smallest percentage (0%) is the public housing affair. Obstacles in the achievement of SPM in the service area of the local government of Pekanbaru city such as the national dynamics, the dynamics of the local scale, the unmixed SPM into the SKPD Rentras, and Still low understanding of the implementation of MSS in SKPD Local Government.